2017
DOI: 10.1097/igc.0000000000000981
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Recovery After Surgery for Advanced Ovarian Cancer: A Systematic Review of Interventions Trialed

Abstract: Few studies have specifically studied ERAS interventions in ovarian cancer. All studies on protocols including multiple interventions were susceptible to bias. Early feeding is the intervention that is best supported by randomized trials. Application of evidence for ERAS derived from nonovarian cancer is challenged by the differences not only in the scope of surgery but also in ovarian cancer patients' comorbidities. Postoperative morbidity is particularly high in these patients because of their poor nutrition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(19 citation statements)
references
References 49 publications
0
19
0
Order By: Relevance
“…A literature search has revealed that few systematic reviews have addressed the current evidence for ERAS in Gynaecological Oncology [21][22][23][24]. These reviews were based on nonrandomised studies and contained high risk of bias and very few studies looked at individual ERAS elements.…”
Section: Discussionmentioning
confidence: 99%
“…A literature search has revealed that few systematic reviews have addressed the current evidence for ERAS in Gynaecological Oncology [21][22][23][24]. These reviews were based on nonrandomised studies and contained high risk of bias and very few studies looked at individual ERAS elements.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence: Early postoperative feeding is defined as resumption of oral fluid and/or solid food intake within 24 hours of surgery. We identified 2 SR limited to patients with gynecologic malignancies 38,39 and 1 MA 40 including Systematic Reviews ajog.org both benign and malignant gynecologic surgery that compared early oral intake to traditional postoperative feeding. In 1 SR that included 7 RCT of 947 oncology patients and 1 observational study, early feeding (as early as 4 hours after surgery) shortened time to flatus and length of stay.…”
Section: Level Of Evidence: Moderatementioning
confidence: 99%
“…In 1 SR that included 7 RCT of 947 oncology patients and 1 observational study, early feeding (as early as 4 hours after surgery) shortened time to flatus and length of stay. 38 The second SR included a different collection of 7 RCT and reported that early oral feeding decreased length of stay in patients undergoing surgery for gynecologic malignancies. 39 Importantly, although early oral feeding was occasionally associated with more nausea in these studies, it did not increase the frequency of vomiting.…”
Section: Level Of Evidence: Moderatementioning
confidence: 99%
“…Only a few randomized trials have been conducted,8 9 and full ERAS protocols have mainly been explored in observational studies that included a broad range of interventions and surgical procedures. Conclusions regarding the efficacy of these protocols have been further based on the comparison with historical controls10 and are therefore highly susceptible to bias. Despite efforts to test single interventions, such as early feeding, in a randomized controlled trial design,11–17 the majority of the guideline recommendations only have a low or moderate level of evidence 6 7.…”
Section: Introductionmentioning
confidence: 99%